Government accountability is in our hands: utilising tech-enabled methodologies to give citizens the power to monitor the implementation of the regulation relating to sexual offences courts - Venter, Tatum (Department of Public Law, 2022)
Given the high incidence of sexual offences in South Africa, effective implementation of legislation aimed at assisting and alleviating the plight of survivors is paramount.1 In February 2020, the Regulation Relating to Sexual Offences Courts (the Regulation) was promulgated. The Regulation provides for the creation of Sexual Offences Courts (SOC) as well as the specialist facilities and services which must be present, there are currently 106 designated courts in South Africa. If properly implemented, the Regulation has far-reaching potential to assist survivors, increase convictions and alter society's perceptions of these offences.2 Monitoring the implementation of the Regulation in Sexual Offences Courts to hold the government accountable and ensure these objects are achieved is of the utmost importance. This pilot study, which was part of an existing project being conducted by a coalition known as Shukumisa, aimed to determine whether an online tool can successfully allow citizens to monitor and collect reliable information on Sexual Offences Courts. In essence, the study built on previous (low-tech, pen-and-paper) attempts to monitor compliance by creating a tech-enabled data collection tool which enabled citizens who are already working within SOCs to monitor the implementation. Overall, the tool was able to successfully monitor the implementation of the Regulation in SOCs and build on previous monitoring projects. With online training, the participants were able to use the tool and effectively monitor the eleven courts in metropolitan as well as outlying areas. The tool had the ability to not only allow monitoring but empower the participants with information and education in an easy and accessible way. With a few minor improvements, it is recommended that the monitoring tool should be rolled out and used to monitor the compliance of every SOC, to hold government accountable to maintain their successes and improve on their downfalls